Ecdysis Triggering Hormone, Eclosion Hormone, and Crustacean Cardioactive Peptide Play Essential but Different Roles in the Molting Process of Mud Crab, Scylla paramamosain - Zhao, Yan-Fei; Wen, Qi-Qiao; Ao, Chun-Mei; Wang, Wei; Shi, Li-Li; Wang, Cheng-Gui; Chan, Siuming-Francis (Frontiers in Marine Science, 2022)
Molting behavior in insects is controlled by the ecdysis triggering hormone (ETH), eclosion hormone (EH) and the crustacean cardioactive peptide (CCAP). At present, the regulation of molting behavior in crustaceans remains unclear. Here, we studied the roles of ETH, EH and CCAP in the molt regulation of the crab, Scylla paramamosain from their expression pattern and in vivo assays. The results showed that transcripts of ETH, EH and CCAP were mainly localized in thoracic ganglia and fluctuated periodically with the molting cycle. When ETH or CCAP was knockdown at early premolt stage (D0), molting of crabs was interrupted and all animals died at late premolt stage (D2). While the EH gene was knock-down, most crabs were dead before D2. Injection of synthetic peptide for ETH or CCAP rescued ETH- or CCAP-gene knock-down crabs separately. However, none of peptides could rescue dsEH-injected crabs. At D0 stage, knockdown of ETH down-regulated the transcriptions of EH and CCAP; while ETH was up-regulated when EH was knockdown. At D2 stage, ETH transcripts levels were reduced with the injection of dsEH but increased with the same dose of dsETH as crabs at D0 stage. Co-injection of dsETH and dsEH down-regulated ETH at D2 stage. Results showed that ETH, EH and CCAP play essential but different roles in molt regulation in mud crab. In summary, the result of this study contributes to the discovery of different molecular mechanisms between Insecta and Crustacea and may provide insight to develop fishery drugs that helps aquacultured crustaceans to molt successfully.